Functional genomics of membrane transporters in human populations - Urban, Thomas J.; Sebro, Ronnie; Hurowitz, Evan H.; Leabman, Maya K.; Badagnani, Ilaria; Lagpacan, Leah L.; Risch, Neil; Giacomini, Kathleen M. (Genome Research, 2006)
Although considerable progress has been made toward characterizing human DNA sequence variation, there remains a deficiency in information on human phenotypic variation at the single-gene level. We systematically analyzed the function of all protein-altering variants of eleven membrane transporters in heterologous expression systems. Coding-region variants were identified by screening DNA from a large sample (n = 247-276) of ethnically diverse subjects. In total, we functionally analyzed 88 protein-altering variants. Fourteen percent of the polymorphic variants (defined as variants with allele frequencies ≥1% in at least one major ethnic group) had no activity or significantly reduced function. Decreased function variants had significantly lower allele frequencies and were more likely to alter evolutionarily conserved amino acid residues. However, variants at evolutionarily conserved positions with approximately normal activity in cellular assays were also at significantly lower allele frequencies, suggesting that some variants with apparently normal activity in biochemical assays may influence occult functions or quantitative degrees of function that are important in human fitness but not measured in these assays. For example, eight (14%) of the 58 variants for which we had measured the transport of at least two substrates showed substrate-specific defects in transport. These variants and the reduced function variants provide plausible candidates for disease susceptibility or variation in clinical drug response.
10.1101/gr.4356206